Theory of Planned Behavior in predicting condom use in Latin-American Women - David Javier Enríquez-Negrete; Ricardo Sánchez-Medina; Susana Xóchitl Bárcena-Gaona; Itzel Guadalupe Chávez-Santos (Interacciones)
Background: The theory of Planned Behavior (TPB) is used to predict condom use. The present study assessed the causal relationships of the TPB in a cultural context different from the one that was proposed. Objective: To assess the causal relationships among the variables proposed by the TCP to determine if they predict consistent condom use in two groups of Latina women and to identify the inter-group similarities in both groups and the discrepancies with what the model proposes for the North American population. Method: A set of variables were evaluated in two samples of Latina women (Mexican and Argentine): consistency of condom use, intention to use condoms in the next sexual encounter, the subjective norm of friends and parents, attitudes towards condoms, and perceived behavioral control to use condoms. We used the Linear regression analysis. Results: Intention to use condoms was found to be the best predictor of condom use. Subjective norm was more important than attitudes; although the latter variable was not configured as a predictor in Argentine women. Conclusion: The associations between the CTP variables and the predictive values of the variables may change according to the cultural group evaluated; perceived behavioral control, in both samples, was not a direct predictor of condom use behavior, but it was a predictor of intention to use condoms. In addition, we discussed the relevance of the variables proposed by the TCP about the cultural context of Latinos and the critical use of the model in populations other than North America.